Land-Use Conflict Dynamics, Patterns, and Drivers under Rapid Urbanization - Guojian Wang; Jianguo Wang; Lingzhi Wang; Yi Zhang; Wenxuan Zhang (Land, 2024)
Conflict over land use is an issue that all countries are experiencing in the accelerated process of urbanization and industrialization. Research on the identification and characterization of land-use conflicts is an important basis for promoting the sustainable development of regional land use. Taking Hebei Province under the background of Beijing–Tianjin–Hebei integration as the research object, this article combines the SCCI model and the LUF model to study the land-use flush in the process of rapid urbanization from the dimensions of land-use landscape conflict and land-use function conflict. The results of this study point out that land-use conflicts in the region have gone through a developmental course of intensification of heavy conflicts, slowing down, and then smoothing out. The exacerbation of land-use conflicts is synchronized with the time pattern of construction and development in the accelerated industrialization and urbanization of Hebei, while the activities of arable land occupation and compensation balance and land ecological management produce lagging land-use conflicts. The spatial pattern is characterized by dispersed and random conflicts in the plains, concentrated conflicts in the mountain stream zones, and stable conflicts in the ecological zones within the mountains in the mountainous areas. The role of externalities and internalities from within the region and in the coordinated development of the region has led to the coexistence of developmental and governance land-use conflicts in Hebei Province, and the geographic environment has a constraining effect on the spatial differentiation of these conflicts. Along with the strong implementation of China’s eco-governance and use-control systems, developmental land-use conflicts from the region will be effectively curbed, but the risk of overlapping developmental conflicts and lagging governance conflicts from coordinated regional development is a key focus for conflict prevention in the future.